2021
DOI: 10.1177/15579883211016361
|View full text |Cite
|
Sign up to set email alerts
|

Men and Oral Health: A Review of Sex and Gender Differences

Abstract: Sex and gender related health disparities in oral health remain an underappreciated and often over looked aspect of well-being. The goal of this narrative review is to identify sex and gender related oral health disparities by summarizing the current literature related to differences in oral health between men and women. The review identified that men are more likely to: ignore their oral health, have poorer oral hygiene habits, and experience higher rates of periodontal disease, oral cancer, and dental trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
115
5
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(144 citation statements)
references
References 54 publications
13
115
5
11
Order By: Relevance
“…It has been reported multiple times in the studies that females tend to have better oral hygiene as compared to males [ 30 ]. This might be due to females tend to visit dentists more often as compared to males and are more concerned about their oral hygiene [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported multiple times in the studies that females tend to have better oral hygiene as compared to males [ 30 ]. This might be due to females tend to visit dentists more often as compared to males and are more concerned about their oral hygiene [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the age is reported in years, which means age may explain more disparity for this association. For sex, previous studies identified that men disproportionately develop periodontal diseases due to a combination of biological and gender related reasons including immune system factors, hormone differences, poorer oral hygiene behaviors, and greater tobacco use [ 23 ]. Compared with women, men also reported a significantly higher prevalence of CHD [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discussions: In this study, the social status of patients was analyzed with the help of indicators that would reflect as objectively as possible the socio-economic level de o neglijare din partea persoanelor de sex masculin a igienei orale, neglijarea faţă de sănătatea orală și adresarea mult mai întârziată după asistenţă medicală. 4 Vârsta, un alt indicator luat în calcul, ne induce următoare părere. Desigur, la pacienţii cu vârsta mai tânără, până la 30 de ani, starea sănătăţii orale este una mai bună, sunt prezente puţine extracţii efectuate sau acestea lipsesc în totalmente.…”
Section: Resultsunclassified
“…The proportion of 2/3 of female patients and 1/3 of male patients who presented to the doctor and wanted to participate in the study, is not determined by an unequal access to dental care, but rather by a negligence on the part of male individuals, oral hygiene neglection, neglection of the oral health and late request for medical care. 4 Age, another indicator taken into account, leads us to the following opinion. In younger patients, up to 30 years, the state of oral health is better, there are few extractions performed or they are completely missing.…”
Section: Resultsmentioning
confidence: 99%